Pelatihan Budidaya Ikan Dan Sayuran Dengan Media Akuaponik Di Kecamatan Sajad Kabupaten Sambas - Sangkala, Sangkala; Agam, Beryaldi; Heriyansah, Heriyansah (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Aquaponic system fish farming in Indonesia is a relatively new technology and is not widely known by fish farmers. Aquaponics system fish farming technology is a combination of fish farming and vegetable crop farming in one unified system. The purpose of this devotion is 1). Providing knowledge, understanding, and skills of the community in making aquaponic cultivation of vegetable and tilapia plants; 2). Provide training on mechanisms and procedures for making tilapia farming businesses aquaponically; 3). Knowing the analysis of tilapia farming business in aquaponics. The implementation of community service (PKM) was carried out on September 5, 2022 and September 11, 2022 at the "Harmonis" Farmer Group consisting of 20 people in Mekar Jaya Village, Sajad District, Sambas Regency using several direct approach methods, namely socialization activities, FGDs, and training. This activity consists of several stages, including 1) Socialization activities for the potential of aquaponics tilapia farming as an alternative livelihood based on community empowerment; 2) training in aquaponics cultivation; 3) training on tilapia cultivation business analysis. The results of the activity showed that the members of the "Harmonis" Farmer Group had known the procedures for cultivating vegetables and tilapia with aquaponic media starting from the preparation stage to the business analysis stage.